Timing of intubation of pediatric hematopoietic cell transplant patients: an international survey - Hume, Janet; Goertzen, Lexie; Avent, Yvonne; Steiner, Marie E.; McArthur, Jennifer; , the Hematopoietic Cell Transplant and Cancer Immunotherapy subgroup of the Pediatric Acute Lung Injury and Sepsis Investigator’s Network (HCT-CI subgroup of PALISI) (Frontiers in Oncology, 2024)
Retrospective data suggest that pediatric hematopoietic cell transplant (HCT) patients placed on non-invasive ventilation (NIV) prior to intubation have increased risk of mortality compared to patients who are intubated earlier in their course. The HCT-CI subgroup of the PALISI Network set out to gain a better understanding of factors that influence clinician's decisions surrounding timing of intubation of pediatric HCT patients.We validated and distributed a brief survey exploring potential factors that may influence clinician's decisions around timing of intubation of pediatric HCT patients with acute lung injury (ALI).Results: One hundred and four of the 869 PALISI Network's members responded to the survey; 97 of these respondents acknowledged caring for HCT patients and were offered the remainder of the survey. The majority of respondents were PICU physicians (96%), with a small number of Advanced Practice Providers and HCT physicians. As expected, poor prognosis categories were perceived as a factors that delay timing to intubation whereas need for invasive procedures was perceived as a factor shortening timing to intubation. Concerns for oxygen toxicity or NIV-associated lung injury were not believed to influence timing of intubation.Discussion: Our survey indicates increased risk of ALI from prolonged NIV and oxygen toxicity in HCT patients are not a concern for most clinicians. Further education of pediatric ICU clinicians around these risk factors could lead to improvement in outcomes and demands further study. Additionally, clinicians identified concerns for the patient's poor prognosis as a common reason for delayed intubation.